An exploratory assessment of the salient strategies employed by Magsasaka at siyentipiko para sa pag-unlad ng Agrikultura (MASIPAG) in their Rice Variety Conservation Program in Barangay Dao, Alimodian, Iloilo a gender analysis - Galanza, Louielyn Gallo
This study focuses on the assessment of the salient strategies employed by MASIPAG in its rice variety conservation program in Barangay Dao, Alimodian Iloilo. Primarily, it aims to address the following objectives: 1)To determine the salient strategies employed in MASIPAG's rice variety conservation program 2) To determine the existing views, treatment and relationship of men and women members according to the roles they assumed in every specific strategy emplyed. 3) To be able to determine the roles and responsibilities of men and women on the program of rice variety conservation. 4) To determine the effect of the strategies in the agricultural yield of the farmers in the area. 5) To determine whether the strategies of Rice Variety Conservation Program have given the male and female farmers to participate in the decision making processes. 6) To determine whether the strategies in Rice Variety Conservation have given male and feamle farmers the opportunity to gain access to traditional seed varieties as well as new knowledge and skills in farming. The study is basically and exploratory and evaluative analysis wherein the data extracted from the KII and secondary data such as literatures were utilized to assess the gender sensitivity of the salient strategies employed in rice variety conservation program of MASIPAG. Furthermore, the respondents were the farmer-resident of Brgy. Dao, Alimodian. Results showed that MASIPAG employed basically three salient strategies. They are; The establishment of people's organization the establishment of trial farm, and the farmer-trainer as a strategy. These strategies have specific activities which are conducted regularly in the area. The strategies employed indeed enhance the participation of male and female farmers, as well as gave them the opportunity to gin traditional seed varieties and as well as enhance their knowledge and skills in farming. Moreover, women's contributions and capacities were highly acknowledge and accepted by men in the area. Lastly, the agricultural yields or harvest of farmers in the area had increased since they started using MASIPAG varieties. The researchers recommend that further in depth study in the area on the gender analysis of the strategies would be made to affirm the result of the study. Moreover, the researchers suggest that MASIPAG should require documentations or activity reports as it is necessary for their future use and as well as for easy access for future researchers who want to study their program. Lastly, MASIPAG should include in their program the conduct of trainings on documentation to enhance and improve the documentation skills of the members within the organization.